Antiviral activity of palmitic acid via autophagic flux inhibition in zebrafish (Danio rerio). Issue 95 (December 2019) - Librán-Pérez, Marta; Pereiro, Patricia; Figueras, Antonio; Novoa, Beatriz
Abstract: Fatty acids (FAs) are key elements that affect not only growth but also different immune functions, and therefore, nutrition is important for growing healthy fish. Zebrafish ( Danio rerio ) is a good model for assessing the beneficial effects of immunostimulants, including FAs, before applying them in aquaculture. Accordingly, this study evaluated the effects of palmitic acid (PA) treatment on different immune parameters of zebrafish and on the mortality caused by the spring viremia of carp virus (SVCV). The results suggest that PA modulates the infection outcome in vivo, which benefits zebrafish and results in reduced mortality and viral titres. The antiviral protection elicited by this FA seems to be associated with the inhibition of autophagy and is independent of other immune processes, such as neutrophil proliferation or type I interferon (IFN) activity. The use of PA as an immunostimulant at low concentrations showed great potential in the prevention of SVCV infections; therefore, this FA could help to prevent the mortality and morbidity caused by viral agents in aquacultured fish. Nevertheless, the potentially detrimental effects of suppressing autophagy in the organism should be taken into account. Highlights: PA enhances resistance against SVCV infection. PA does not affect type I IFN expression or neutrophil counts. PA inhibits autophagosome/lysosome fusion. The anti-SVCV effect mediated by PA is, at least in part, related to inhibited autophagy.